CONFLICT IN JOHN RONALD REUEL TOLKIEN’S NOVEL LORD OF THE RINGS: THE FELLOWSHIP OF THE RING - Daeli, El Nitari; Manugeren, M. (JOURNAL OF LANGUAGE, 2024)
This study explores the intricate conflicts experienced by the protagonist in J. R. R. Tolkien's epic masterpiece, The Lord of the Rings: The Fellowship of the Ring. Focused primarily on internal and external conflicts, the narrative follows a fellowship of nine individuals united by their quest to destroy the malevolent Ring, possessed by the dark lord Sauron, in the fiery depths of Mount Doom. Throughout their journey, the protagonist grapples with multifaceted challenges, providing rich material for analysis. Employing a literary psychological approach, this study draws upon Kenney's theory of conflict typologies to explore the protagonist's inner turmoil and the adversities encountered externally. Utilizing a descriptive qualitative method, the research meticulously examines these conflicts to unveil their profound significance within the narrative. The findings of the study underscore the protagonist's dual struggle, comprising internal and external conflicts. Internally, the protagonist contends with the classic conflict of man versus himself, navigating doubts, fears, and moral dilemmas. Externally, a complex web of conflicts unfolds, encompassing interpersonal clashes (man versus man), societal discord (man versus society), and the formidable forces of nature (man versus nature). By dissecting these conflicts, the study illuminates the psychological and narrative depths of Tolkien's work, revealing the protagonist's arduous journey as a reflection of universal human struggles against both inner demons and external adversities.